Analisis Cost Volume Profit sebagai Alat Bantu Manajemen dalam Rangka Perencanaan Laba dengan Penerapan Teori Kendala pada PT Skylite Surya Internusa - Deviarti, Holly; Ayu, Melati (Binus Business Review, 2011)
PT Skylite Solar Internusa is an industrial company that produces the houses lights and panel box. The purpose of this study is to help companies classify costs according to the behavior of costs, determine the calculation of the break event point of multiproduct, profit planning, and to overcome the constraints that occured in the company. The authors obtained data directly to the companys research and interviews with relevant parties, such as the production and the accounting department. The increase in profit in the fiscal year period 2009 due to demand for homes increased light and panel box. It can be concluded that the application of Cost-Volume-Profit analysis by using the break event point multiproduct can help management to determine how much sales volume may decline from the volume of sales is budgeted by the company and the company can make profit plan in 2010.